Human Flourishing and a Theology of Poverty Alleviation - Reize, Nikayla (International journal of public theology, 2021)
Abstract The Christian Scriptures present an idealized vision for human flourishing that includes material and economic justice, as well as relational, spiritual wholeness. This binds Christians to a non-negotiable responsibility to work to prevent and alleviate poverty as an act of participation in God’s redemption of creation. Key to this work is an appropriate and accurate understanding of human flourishing (and its corollary, human poverty) as multi-dimensional. Consequently, any Christian theology that seeks to address the prevention and alleviation of poverty must also explore the necessary issues from a multi-dimensional perspective. While there are diverse ways in which Christians can participate in this divine work, a Christian vision for the alleviation and elimination of poverty must have a focus on long-term structural solutions to injustice, and the importance of community and relationship. This article gives particular attention to a Canadian context. (150 words only)